Here to stay? The rapid evolution of the temporary staffing market in Iceland - Magnússon, Gylfi; Minelgaite, Inga; Kristjánsdóttir, Erla S.; Christiansen, Þóra H. (Stjórnsýslustofnun, 2018)
In recent years there has been a significant shortage of workers in Iceland. The traditional method of arranging temporary work, through direct contracts between employees and employers, has not sufficed. Moreover, there is a skills mismatch that compounds the shortage of workers as the sectors that have grown most rapidly in recent years mainly employ unskilled labor. This study examined the historical background of temporary work in Iceland, recent developments and in particular the growing importance of temporary staffing agencies, as well as the economic rationale for temporary staffing agencies, and the segmented labor market in Iceland. The study employs expert opinion approach, together with content and statistical analysis. Experts placed strongest emphasis on temporary workforce dependency on economic conditions, closely followed by sector triggered temporary workforce fluctuation. Socio-legal infrastructure for temporary workforce had the third strongest emphasis with other themes being less emphasized. These dramatic changes to the Icelandic labor market have undoubtedly had a significant impact on Icelandic society but there is surprisingly little research available into this. The efforts of unions and the Federation of Employees have helped to push through legislation on temporary staffing agencies and the rights of foreign workers, however, as long as there is economic rationale for their operation and a legal and regulatory framework that accommodates them the agencies can be expected to continue bringing temporary staff to Iceland. The impact on the labor market and society thus seems likely to be permanent.